“Micropropagación de Ananas comosus (L.) merr. Cultivar MD-2 “Golden”, mediante un sistema de inmersión temporal” - Alverca Gálvez, Wagner (2015)
This research aimed to determine an efficient protocol for micropropagation of Ananas comosus {L.) Merr, growing MD-2 "Golden" through a temporary immersion system, in order to determine the number of explants allow to obtain a high rate of multiplication of shoots and get the largest number of seedlings with high enough for acclimatization stage. The research was conducted at the Laboratory of Plant Biotechnology of the Agricultura! Experimental Station "El Porvenir'' - Tarapoto - INIA located in the district Juan Guerra 14.5 km from the city of Tarapoto, via highway Femando Belaunde Terry {Tarapoto - Juanjui). The design was completely randomized {CRD) with three treatments under study and each treatment with three replications or observations. In each iteration we were evaluated 7, 10 and 13 explants, resulting in a total of 21, 30 and 39 seedlings per treatment evaluated respectively. (EU) experimental unit was constituted by a BIT unit {a bottle containing the explants over a bottle for the liquid medium). Pollution, number of plants obtained by treatment, number of seedlings by treatment class, height plantlets per treatment, survival {versus seedlings plantad seedlings acclimated according to class): After 16 weeks of culture the following variables were evaluated. The results indicate that the T3 {13 explants I BIT) treatment had the highest average seedling {361) number, followed by T2 and T1 treatment, who obtained 225 and 177.8 average seedlings, respectively. However, in the treatment T2 {10 explants I BIT), eamed the highest average height of seedlings with 6.6 cm., Followed by T3 and T1 treatments, who obtained averages of 5.7 and 5.5 cm seedling, respectively. Keywords: Protocol, micropropagation, dipping, explants, rate, multiplication, sprouts, seedlings.